Synbiotic and protein-enriched low-fat Sao Hai rice ice cream - Putthapong Phumsombat; Kulanid Trisakwattana; Natcha Ittithanaput; Natchanan Viwatanawatanakarn; Chaleeda Borompichaichartkul (Quality Assurance and Safety of Crops & Foods, 2024)
This research aimed to investigate the production of low-fat Khao Sao Hai ice cream fortified with synbiotics, soy protein (SP), and chicken breast protein. The study incorporated Sao Hai rice milk into the ice cream formulations and conducted experiments to analyze the physical, chemical, and sensory characteristics. The application of synbiotic powder, SP, and chicken breast protein was explored, with the results indicating significant variations in the nutritional profile. Specifically, ice cream fortified with chicken breast protein exhibited the highest protein content at 4.20 g, followed by SP at 3.92 g, and the control formulation at 1.38 g. In addition, the survival rate of probiotics, represented by Lactobacillus acidophilus LA5, exceeded 98% during storage at −20°C for 21 days, showcasing the successful encapsulation of probiotics with Konjac glucomannan and soy protein isolate. Furthermore, sensory testing revealed that the control formula received the highest consumer acceptance, followed by SP–fortified ice cream. In contrast, chicken breast protein–fortified ice cream received the least acceptance. These findings highlight the potential of Sao Hai rice in creating nutritionally diverse ice cream formulations, offering insights into consumer preferences and the efficacy of different protein sources in enhancing ice cream quality.
Keywords: GABA and Rice Research; Food Quality and Safety Studies; Meat and Animal Product Quality